Thermal Cycle Simulation of Welded Products with Heat Treatment Process on AISI 1015 Low Carbon Steel - Aa Santosa; Tedi Heryanto; Iman Dirja; fahri rizki (Jurnal Mekanika dan Manufaktur, 2026)
In the welding of carbon steel, the cooling time from the highest temperature or peak temperature can be identified, where the cooling rate is generally represented in a welding thermal cycle. Knowledge of the welding thermal cycle greatly facilitates the understanding of the extent of differences in cooling rates at various applied peak temperatures. The thermal cycle curve can be obtained through direct testing methods, namely by measuring the temperature on the welded plate. However, this method requires extensive equipment and a high level of precision. Therefore, the author conducted an experiment to obtain the thermal cycle curve using an alternative method. This method involves heat treatment, in which the cooling process is carried out in free air (normalizing) while varying the peak temperature for each specimen. The specimens used in this study were AISI 1015 low-carbon steel, with dimensions of 100 × 20 × 20 mm for the larger specimens and 50 × 20 × 20 mm for the smaller specimens. The applied peak temperatures were 750°C, 800°C, 900°C, and 1000°C. The experimental results showed that the cooling rate obtained through the heat treatment process was inversely proportional to that of the welding process. Therefore, determining the thermal cycle using the heat treatment process is not recommended.